Atividade da fração hidrometanólica de milheto sobre alguns aspectos do metabolismo e crescimento de amendoim-bravo - Silva, Hingrid Ariane da (2013)
Wild poinsettia (Euphorbia heterophylla) is a weed present in every area of crops as soybean, and it has a high potential to reduce productivity and profitability of this plant species. Due resistance records of this and other weeds to the diverse mechanisms of herbicides action, alternatives management of weeds has been studied. Therefore, allelopathy has deepened in studies with use of cover crops to control the most diverse weed. Pearl millet (Pennisetum glaucum) is a cover crop used in animal feed as well as reclamation land degraded which have caused suppression of weed growth, thus showing great potential for this purpose. For evaluate a possible activity allelopathic, millet extracts were obtained by organic solvents. Hydromethanolic extract, the fraction more active, was used for growth assays, evaluation of enzymes activity of phenylpropanoid pathway (phenylalanine ammonia lyase and cell wall-bound peroxidase) and oxidative stress (soluble peroxidase and lipid peroxidation) of wild poinsettia, roots cell viability and scanning electron microscopy (SEM), absorption of nutrient solution, nitrate and ammonia. Wild poinsettia growth was greatly reduced well as activity of phenylalanine ammonia lyase and cell wall-bound peroxidase (p<0.05). Swelling and root elongation zone reduction were noted. This symptom can be result of accelerated cell division, stimulated by allelochemicals from hydromethanolic fraction. Damage in the roots caused by extract were visible by SEM and confirmed through reduction in cell viability (p<0.05) and may have caused the collapse in absorption of ions and nutrient solution. Oxidative stress has not been observed in the plants.